2019
DOI: 10.1073/pnas.1911393116
|View full text |Cite
|
Sign up to set email alerts
|

Combined mTORC1/mTORC2 inhibition blocks growth and induces catastrophic macropinocytosis in cancer cells

Abstract: The mammalian target of rapamycin (mTOR) pathway, which plays a critical role in regulating cellular growth and metabolism, is aberrantly regulated in the pathogenesis of a variety of neoplasms. Here we demonstrate that dual mTORC1/mTORC2 inhibitors OSI-027 and PP242 cause catastrophic macropinocytosis in rhabdomyosarcoma (RMS) cells and cancers of the skin, breast, lung, and cervix, whereas the effects are much less pronounced in immortalized human keratinocytes. Using RMS as a model, we characterize in detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 60 publications
1
39
0
Order By: Relevance
“…Meanwhile, the results of the latest clinical trial suggest the benefit of additional temsirolimus therapy in comparison with bevacizumab [ 18 ]. Further improvement is expected via using dual inhibitors, since these can overcome rapalog resistance by targeting both the mTORC1 and the C2 complexes or the PI3K-mTOR pathway simultaneously [ 5 , 35 , 36 , 37 ]. Some investigations have reported the strong inhibitory effect of mTORC1/2 dual inhibitors in vitro as well.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the results of the latest clinical trial suggest the benefit of additional temsirolimus therapy in comparison with bevacizumab [ 18 ]. Further improvement is expected via using dual inhibitors, since these can overcome rapalog resistance by targeting both the mTORC1 and the C2 complexes or the PI3K-mTOR pathway simultaneously [ 5 , 35 , 36 , 37 ]. Some investigations have reported the strong inhibitory effect of mTORC1/2 dual inhibitors in vitro as well.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous study in rhabdomyosarcoma cells indicated that while mTORC1 inhibition (rapamycin treatment) or mTORC2 inhibition (Rictor knockdown) alone had little effect, combined inhibition of mTORC1 and mTORC2 effectively inhibited tumour growth (Srivastava et al . 2019). Interestingly, muscle contraction increased SGK1 expression, and this effect was attenuated by combined Rictor mKO and rapamycin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The mTOR pathway is often disrupted in cancers, and the intersection between mTOR and TPCs suggests intriguing therapeutic possibilities (197). In cancers associated with skin, breast, lung and cervix, and rhabdomyosarcoma (RMS), Srivastava et al found that the use of dual mTORC1/mTORC2 inhibitors, OSI-027 and PP242, resulted in over-activation of macropinocytosis, inhibiting tumor survival (24). In further experiments, xenograft RMS in mice treated with OSI-027 showed reduced tumor growth, reduced proliferation, and excessive macropinocytosis in cancer cells.…”
Section: Cell Metabolism Reducing Under Macropinocytosis Inhibitionmentioning
confidence: 99%
“…In particular, Kim et al discovered that macropinocytosis can promote the survival of malnourished PTEN-deficient prostate cancer cells (21). In recent years, studies have reported that plasma membrane vacuolar ATPase (V-ATPase) (22), Syndecan 1 (SDC1) (23), mTORC1/mTORC2 (24), and epidermal growth factor receptor (EGFR) pathways (25) are closely associated with the molecular mechanism of macropinocytosis in tumor cells. In addition, the C-Jun N-terminal kinase (JNK) signaling pathway played a key role in methuosis (26).…”
Section: Introductionmentioning
confidence: 99%